A 'Friend and Advisor': Management, Auditors, and Confidence in Germany's Credit Cooperatives, 1889-1914 - Timothy W. Guinnane (Yale University, Economic Growth Center, 2001)
Economic enterprises face two, related, managerial problems: effective management of the enterprise's activities, and communicating to outsiders that the enterprise is in fact well-run. These problems were especially difficult in the credit cooperative movement that grew up in Germany in the second half of the nineteenth century. These successful cooperatives thrived because they could harness the information and ties among local people to obviate many of the problems that faced other lenders. Doing so required managers who were themselves local people. Yet few if any locals had any banking experience, and most were not even familiar with basic accounting methods. These local managers created internal management problems and enhanced outside suspicion of the cooperatives as banking enterprises. The methods developed to overcome these problems relied on a combination of local initiative and regional assistance that was typical of the movement as a whole. The movement's ability to train its own talent suggests a broader impact not captured by statistics on membership or financial assets.
Keywords: G2; N23; O16; 330; credit cooperative; external audit; Genossenschaftsbank; Deutschland